The impact of the COVID-19 pandemic on the medical care and health-care behaviour of patients with lupus and other systemic autoimmune diseases: a mixed methods longitudinal study. Issue 1 (14th December 2020) - Sloan, Melanie; Gordon, Caroline; Harwood, Rupert; Lever, Elliott; Wincup, Chris; Bosley, Michael; Brimicombe, James; Pilling, Mark; Sutton, Stephen; Holloway, Lynn; D'Cruz, David
Abstract: Objective: The aim was to explore the self-reported impact of the COVID-19 pandemic on changes to care and behaviour in UK patients with systemic autoimmune rheumatic diseases, to help ensure that patient experiences are considered in future pandemic planning. Methods: This was a longitudinal mixed methods study, with a cohort completing baseline surveys in March 2020 and follow-up surveys in June 2020 ( n = 111), combined with thematic analysis of the LUPUS UK forum and participant interviews ( n = 28). Results: Cancellations of routine care and difficulties in accessing medical support contributed to some participants deteriorating physically, including reports of hospitalizations. The majority of participants reported that fear of COVID-19 and disruptions to their medical care had also adversely impacted their mental health. Feeling medically supported during the pandemic was correlated with multiple measures of mental health and perceptions of care, including the Warwick–Edinburgh mental well-being score ( r = 0.44, P = 0.01). Five themes were identified: detrimental reduction in care; disparities in contact and communication (medical security vs abandonment sub-theme); perceived and actual endangerment; the perfect storm of reduced clinician ability to help and increased patient reticence to seek help; and identifying the patients most vulnerable to reduced medical care. Conclusion: The diversion of resources away from chronic disease care was perceived by many participants to have caused adverse outcomes. Fear about increased vulnerability to COVID-19 was high, contributing to health-care-avoidant behaviours. This study also highlights the influence of clinician accessibility and patients feeling medically supported on multiple measures of physical and mental health.